The Perception of the People of Medan Towards the Police in Combating Mugging Crimes - Ramadhan Yoga Pamungkas (Indonesian Journal of Communication and Social, 2025)
This research stems from the increasing problem of street crimes, particularly “begal” (armed robbery or motorcycle hijacking), which has claimed victims’ lives in Medan City. The study aims to provide an overview of the public’s perception of the police in combating begal crimes in Medan. The research employs a qualitative approach, with data collected through interviews with residents who are familiar with police performance in addressing begal cases, direct observation of related activities, and documentation of the interviews. The data analysis technique follows the Miles and Huberman model, which consists of three concurrent activities: data reduction, data display, and conclusion drawing/verification. The study was conducted in Medan with six (6) informants residing in the city. The findings indicate that the perception of Medan residents regarding police performance in tackling begal crimes remains unsatisfactory. The main concerns include the infrequency of police patrols, limited collaboration with the community, and slow responses to public reports.